KOMPOSISI JENIS TUMBUHAN BAWAH DI HUTAN ALAM GIRIMANIK WONOGIRI - , DESI FIKIWIJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesian forest plantations not only, but there are also natural forests that would have abundant biodiversity. Constituent of forest vegetation in natural forests not only the level of seedlings, saplings, poles and trees, but some plants undergrowth the stands with a height approximately 150 cm or 1.5 m. The existence of natural undergrowth and saplings are very important due to the continuity and preservation of ecological functions. Research has the objective to determine the composition of plant species and to determine the type under which domination in natural forest areas. The study was conducted at the Natural Forest Girimanik Wonigiri in Lawu the foot of the mountain is in the region of Surakarta management, BKPH South Lawu. Research using methods that do make the plot in any altitude ranging from 1300 to 1600 m dpl. So as to know the composition is in each altitude for natural seedlings and plants at the site under study, it can calculate the important value index based Dombois and Ellenberg 1974 and determine the dominant species in the region. From the research to important value index of each activity performed penelitain obtained the highest in undergrowth of 27.56% found in the type Eclipta alba), with a relative frequency of 18.03% and the relative density of 9.53%. Important value index describe the level of dominance of plants in an area. So based on the calculation, it can be in the know important value index highest value is the type that predominates in the area.